Dual-responsive recurrent self-assembly of a supramolecular polymer based on the host–guest complexation interaction between β-cyclodextrin and azobenzene. (7th February 2018) - Shen, Ping; Qiu, Liyan
Abstract : A novel supramolecular polymer PAE- g -Azo@β-CD-PEG was constructed, which significantly displayed pH- and photo-dual-responsive recurrent self-assembly behaviors. Abstract : In this work, we report a supramolecular polymer based on the host–guest interaction between β-cyclodextrin groups in β-CD-PEG and azobenzene groups in PAE- g -Azo. The supramolecular polymer PAE- g -Azo@β-CD-PEG could self-assemble into a regular nanostructure in aqueous solution due to its proper amphiphilicity. Benefiting from the pH-responsiveness of PAE and the photo-responsive trans -to- cis isomerization of Azo, the supramolecular assemblies apparently show pH and photo responsive properties. Furthermore, the combination of the pH regulation and the irradiation of UV light or visible light induced the recurrent disassembly and reassembly of the supramolecular polymer. This dual-responsive supramolecular polymer has great prospects in various practical applications such as intelligent nanomaterials and nanotechnology.